Tendon elasticity: Latest findings and state of the art - Albracht, K. (7th European Pole Vault and High Jump Conference, Cologne, November 11-13, 2016, 2016)
- tendons material properties play an important role in athletic performance! - optimal tendon stiffness is task specific and depends on the mechanical and morphological properties of the MTU. - tendons have the potential to adapt (CSA, material properties), "Training a tendon" -» high strain, moderate duration. - tendons' response to training is later than that of muscle.